Single crystal growth and physical properties of superconducting ferro-pnictides Ba(Fe, Co)2As2 grown using self-flux and Bridgman techniques - Aswartham, Saicharan; Nacke, C.; Friemel, G.; Leps, N.; Wurmehl, S.; Wizent, N.; Hess, C.; Klingeler, Rüdiger; Behr, G.; Singh, S.; Büchner, B. (Journal of crystal growth, 2011)
We have employed the high temperature solutions growth technique and the Bridgman technique to grow cm-size high-quality single crystals of pristine BaFe2As2 (Ba122) and its Co-doped superconducting variants. In the first approach, self-flux (Fe, Co)As was used to achieve a homogeneous melt of composition Ba(Fe, Co)3.1As3.1 at T=1463K. The melt was then cooled slowly under a temperature gradient in a double-wall crucible assembly to obtain large and flux-free single crystals of Ba(Fe, Co)2As2. In the second approach, single crystals were grown directly from a stoichiometric Ba(Fe, Co)2As2 melt at T=1723K employing the Bridgman technique associated with a vertical tube furnace. Using both techniques single crystals with lateral dimensions up to 25×10mm2 and thickness up to 1mm were obtained. Details of the two methods are given and a comparative study of the magnetic and transport properties of the single crystals obtained using the two methods is presented.